Characterization of lattice parameters gradient of Cu(In1-xGax)Se2 absorbing layer in thin-film solar cell by glancing incidence X-ray diffraction technique. (15th August 2020) - Kim, Yong-Il; Kim, Ki-Bok; Kim, Miso
Abstract: In or Ga gradients in the Cu(In1-x Gax )Se2 (CIGS) absorbing layer lead to change the lattice parameters of the absorbing layer, giving rise to the bandgap grading in the absorbing layer which is directly associated with the degree of absorbing ability of the CIGS solar cell. We tried to characterize the depth profile of the lattice parameters of the CIGS absorbing layer using a glancing incidence X-ray diffraction (GIXRD) technique, and then investigate the bandgap grading of the CIGS absorbing layer. When the glancing incident angle increased from 0.50 to 5.00°, the a and c lattice parameters of the CIGS absorbing layer gradually decreased from 5.7776(3) to 5.6905(2) Å, and 11.3917(3) to 11.2114(2) Å, respectively. The depth profile of the lattice parameters as a function of the incident angle was consistent with vertical variation in the compositionof In or Ga with depth in the absorbing layer. The variation of the lattice parameters was due to the difference between the ionic radius of In and Ga co-occupying at the same crystallographic site. According to the results of the depth profile of the refined parameters using GIXRD data, the bandgap of the CIGS absorber layer was graded over a range of 1.222–1.532 eV. This approach allows to determine the In or Ga gradients in the CIGS absorbing layer, and to nondestructively guess the bandgap depth profile through the refinement of the lattice parameters using GIXRD data on the assumption that the changes of the lattice parameters or unit-cell volume follow a good approximation to Vegard's law.